2011
DOI: 10.1017/s0144686x11000419
|View full text |Cite
|
Sign up to set email alerts
|

Baby-boomers and the ‘denaturalisation’ of care-giving in Quebec

Abstract: The North American post-war generation, known as the baby-boomers, has challenged traditional family relations and the sexual division of labour. How do these challenges play out in the face of frail, ill or disabled family members? A study undertaken in Montreal, Quebec, with baby-boomer care-givers aimed to raise understanding of the realities of this group. We met with  care-givers for a one and a halfhour qualitative interview to discuss their identification with their social generation, their relationsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
12

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 19 publications
(18 reference statements)
0
4
0
12
Order By: Relevance
“…Although social and political-economic discourses that prioritize family responsibility as a moral imperative have been well documented, particularly for women (Binney and Estes, 1988;Hooyman and Gonyea, 1995;Armstrong and Kits, 2004), it has also been suggested that in post-industrial North America, structural and cultural processes reflect a pattern of individualization (Beck and Beck-Gernsheim, 2001). As such, individuals may increasingly interpret family relationships as being most appropriately rooted in choice and affection, rather than obligation (Beck and Beck-Gernsheim, 2001;Fine, 2005;Guberman, Lavoie, and Olazabal, 2011). Although participants in the present study supported a moral imperative of filial responsibility to some extent, responsibility (as obligation) did not always fit with their portrayals of family relationships, and choice was a dominant theme throughout their accounts.…”
Section: Discussionmentioning
confidence: 64%
“…Although social and political-economic discourses that prioritize family responsibility as a moral imperative have been well documented, particularly for women (Binney and Estes, 1988;Hooyman and Gonyea, 1995;Armstrong and Kits, 2004), it has also been suggested that in post-industrial North America, structural and cultural processes reflect a pattern of individualization (Beck and Beck-Gernsheim, 2001). As such, individuals may increasingly interpret family relationships as being most appropriately rooted in choice and affection, rather than obligation (Beck and Beck-Gernsheim, 2001;Fine, 2005;Guberman, Lavoie, and Olazabal, 2011). Although participants in the present study supported a moral imperative of filial responsibility to some extent, responsibility (as obligation) did not always fit with their portrayals of family relationships, and choice was a dominant theme throughout their accounts.…”
Section: Discussionmentioning
confidence: 64%
“…Guberman et al (2011) suggest that baby boomers consider their caring responsibilities as a role in itself, a shift from the perspective of their parent generation who perceived these as an aspect of their natural roles of mother, daughter, or wife. Furthermore, baby boomer caregiving women voice the importance to maintain their other activities, paid work and social activities, and not having to sacrifice those to take on caregiving, although, in practice, many do make a considerable amount of changes in their professional and personal lives as a consequence of caregiving.…”
Section: Changes In Proportions Of Caregivers Across Birth Cohortsmentioning
confidence: 99%
“…Toutefois, différentes analyses menées par Nancy Guberman et Jean-Pierre Lavoie montrent que les familles refusent largement ce retournement (Guberman et al, 2006 ;Guberman, Lavoie et Olazabal, 2011 ;Lavoie et al, 2003). Les proches considèrent généralement que leur rôle est d'assurer le soutien affectif et social de l'aîné et de veiller au bon fonctionnement des différents services assurés par le public et en aucun cas de devenir…”
Section: Brouillage Des Frontières Entre Le Familial Et Le Professionnelunclassified